Crucial Stepping Stones in Platelet History - Hvas, Anne-Mette (Seminars in Thrombosis and Hemostasis, 2022)
This review summarizes the time that has passed from the initial registration of the cells that turned out to be platelets up to today's advanced methodologies in platelet investigation. The first reports of “granular masses” appeared in the 1840s, but these “granular masses” remained an unsolved mystery until the 1870s. The breakthrough came in the 1873–1882 period. The cells that later turned out to be platelets were further identified by the German Professor Max Schultze, and later by Osler, who described their disk-like structure. These initial descriptions of platelets were expanded by impressive studies performed by the Italian Pathologist Bizzozero who uncovered the anatomy of platelets and described their role, first in experimental thrombosis and later in the clotting process. Nearly 20 years later, in 1906, Wright published the discovery of megakaryocytes as platelet precursors. Shortly thereafter, the clinical proof of concept illustrating the pivotal role of platelets in arresting bleeding was revealed by Duke who introduced the bleeding time test, also in this period. To investigate platelet function more specifically, light transmission aggregometry was introduced in 1962 and remains the gold standard today. This method inspired the development of several devices employing whole blood using different principles for evaluating platelet function. As of today, flow cytometry is the most advanced method and holds promise to provide new insights into platelet activation. Additionally, advances in genetic testing by the use of next-generation sequencing will allow further improvement of our ability to diagnose inherited platelet disorders.
Keywords: blood platelets; hemostasis; history of medicine